DIRECT AND COOPERATIVE LEARNING STRATEGIES: THEIR ADVANTAGES AND IMPLEMENTATION IN INCREASING INTEREST IN LEARNING - Rotua Samosir (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
The effectivity and efficiency of student learning and learning in schools is highly dependent on the role of the teacher. One of his ideal teachers acts as a conservator, transmitter, transformer, and also an organizer. In some elementary schools in Tarutung, the values of Christian education have not colored the entire dynamics of life and the teaching and learning process. This happens because so far there has not been a program created by the school to provide guidance and supervision specifically on the growth of spirituality to both students and teachers as Christian educators in the school. This study aims to prove the influence of direct learning strategies and cooperative learning strategies on the interest in learning Christian Religious Education in elementary schools in the Tarutung area. This research is a quantitative research with the Experiment One-Group Pretest-Posttest Design approach. From the results of the study, it was obtained that the significance value of the Paired Sample T-Test direct learning strategy and cooperative learning strategy limited tothe interest in learning Christian Religious Education kurang from 0.05 (p < 0.05), showed a significant influence between the learning strategy and the interest in learning. Other factors that also influence the growth of student interest in learning include internal factors such as physical condition, psychological, and fatigue, as well as external factors such as the way the teacher teaches, the material/subject matter delivered, the purpose of teaching, the media used by the teacher in teaching and the surrounding environment.